An in vitro model to study heterogeneity of human macrophage differentiation and polarization - Erbel, Christian; Rupp, Gregor Fabian; Helmes, Christian Michael; Tyka, Mirjam Evelin; Linden, Fabian; Dösch, Andreas; Katus, Hugo; Gleißner, Christian A. (JoVE. Science education, 2013)
Monocyte-derived macrophages represent an important cell type of the innate immune system. Mouse models studying macrophage biology suffer from the phenotypic and functional differences between murine and human monocyte-derived macrophages. Therefore, we here describe an in vitro model to generate and study primary human macrophages. Briefly, after density gradient centrifugation of peripheral blood drawn from a forearm vein, monocytes are isolated from peripheral blood mononuclear cells using negative magnetic bead isolation. These monocytes are then cultured for six days under specific conditions to induce different types of macrophage differentiation or polarization. The model is easy to use and circumvents the problems caused by species-specific differences between mouse and man. Furthermore, it is closer to the in vivo conditions than the use of immortalized cell lines. In conclusion, the model described here is suitable to study macrophage biology, identify disease mechanisms and novel therapeutic targets. Even though not fully replacing experiments with animals or human tissues obtained post mortem, the model described here allows identification and validation of disease mechanisms and therapeutic targets that may be highly relevant to various human diseases.
Gesehen am 17.02.2021
Enthält auch Textversion
Wissenschaftlicher Film. Deutschland. 2013
Keywords: Film